LENGTH-WEIGHT RELATIONSHIP AND OTHER DIMENSIONAL RELATIONSHIPS OF METAPENAEUS MONOCEROS (FABRICIUS) FROM THE KAKINADA COAST - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
Information on length-weight relation ofprawns is needed in studies on growth andsexual maturity and for obtaining yieldestimates by analytical models. Similarlyinformation on carapace length—total length,total length—total weight and total weight—tail relations is needed to compare datafrom different sources since information oncatch statistics is recorded in various unitsdepending on local marketing practices.